Російська дезінформація у Європейському Союзі: виклики та протидія - Рожков, Андрій Ігорович (Протидія дезінформації в умовах російської агресії проти України: виклики і перспективи: тези доп. учасників міжн. наук.-практ. конф. (Анн-Арбор - Харків, 12-13 груд. 2023 р.), 2023)
The article discusses the challenges faced by the European Union in combating Russian disinformation against Ukraine. The Russian Federation uses a variety of tactics and platforms to spread disinformation in the EU. The purpose of this information is to undermine support for Ukraine, justify Russian aggression and conceal war crimes. The article substantiates its claims with examples of disinformation campaigns and statistics from EU media and research centers. The facts presented in the article are evidence that Russian disinformation poses a significant threat to the EU and its citizens, potentially weakening EU solidarity and resilience, distorting public discourse and manipulating public sentiment. Increasing the effectiveness of countering Russian propaganda can be achieved by increasing funding and staffing of working groups such as East StratCom, implementing the Digital Services Act, and strengthening strategic communication and critical thinking in society.